You don't need to forgive : trauma recovery on your own terms - Gregory, Amanda Ann (Broadleaf Books, 2025)
"Feeling pressured to forgive offenders is a common reason why trauma survivors avoid mental health services and support. Trauma psychotherapist Amanda Ann Gregory explores the dangers of forced forgiveness and the benefits of elective forgiveness, which gives survivors the agency to progress in their recovery on their own terms"-- Provided by publisher.
Keywords: Forgiveness -- Psychological aspects.; Psychic trauma -- Treatment.; Pardon -- Aspect psychologique.; Traumatisme psychique -- Traitement.